2019
DOI: 10.3390/ijms20194728
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of a Novel Tyrosine Kinase Inhibitor AIU2001 Due to Abrogation of the DNA Damage Repair in Non-Small Cell Lung Cancer Cells

Abstract: Class III receptor tyrosine kinase (RTK) inhibitors targeting mainly FLT3 or c-KIT have not been well studied in lung cancer. To identify a small molecule potentially targeting class III RTK, we synthesized novel small molecule compounds and identified 5-(4-bromophenyl)-N-(naphthalen-1-yl) oxazol-2-amine (AIU2001) as a novel class III RKT inhibitor. In an in vitro kinase profiling assay, AIU2001 inhibited the activities of FLT3, mutated FLT3, FLT4, and c-KIT of class III RTK, and the proliferation of NSCLC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Here, we showed that 7c inhibited FLT3-STAT5 signaling as well as HR and NHEJ DNA repair genes, probably contributing to the growth inhibition and death of FLT3-ITD + AML cells. These results are consistent with those of our previous study, in which we demonstrated that the inhibition of STAT5 downregulates DNA repair [11]. Previous studies suggested that AML with genomic instability is sensitive to PARP inhibition [10,20].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Here, we showed that 7c inhibited FLT3-STAT5 signaling as well as HR and NHEJ DNA repair genes, probably contributing to the growth inhibition and death of FLT3-ITD + AML cells. These results are consistent with those of our previous study, in which we demonstrated that the inhibition of STAT5 downregulates DNA repair [11]. Previous studies suggested that AML with genomic instability is sensitive to PARP inhibition [10,20].…”
Section: Discussionsupporting
confidence: 94%
“…Inhibition of FLT3-ITD function by quizartinib reduces two major DSB repair activities with homologous recombination (HR) and nonhomologous end-joining (NHEJ). Our previous study supported that quizartinib and the novel FLT3 inhibitor AIU2001 downregulate DNA repair HR and NHEJ genes [10,11]. To investigate whether 7cinduced AML cell death was caused by the inhibition of DNA damage repair pathways, we determined the expression levels of HR and NHEJ genes in Molm-13 and MV4-11 cells.…”
Section: C Suppressed Dna Damage Repairmentioning
confidence: 74%
See 1 more Smart Citation
“…Cell lysates were prepared by extracting proteins with TNN buffer (40 mM Tris-Cl pH 8.0, 0.2% NP-40, 120 mM NaCl) supplemented with a protease inhibitor cocktail (Thermo Fisher Scientific, Rockford, IL, USA). Western blot analysis was performed as previously described [ 32 ]. Details of the primary antibodies used in this study are provided in the Supplementary Materials and Methods section .…”
Section: Methodsmentioning
confidence: 99%
“…This results in synthetic lethality with PARPi. 100 , 101 In addition, c-MET and EGFR, both similar RTKs, were also found to be hyperactivated in TNBC cells with acquired resistance to PARPi. This is presumably because EGFR and MET heterodimers interact with and phosphorylate the Tyr907 residue of PARP1.…”
Section: Parpi Resistance and Overcoming Strategiesmentioning
confidence: 97%